Increasing Arabic Vocabulary Mastery Through Gamification; is Kahoot! Effective? - Agus Riwanda; Muhammad Ridha; M Irfan Islamy (LISANIA: Journal of Arabic Education and Literature, 2021)
Vocabulary (mufradat) mastery is decisive in the success of foreign language learning. Mastering many vocabularies can improve students’ listening, speaking, reading, and writing skill. Various strategies have been applied to improve vocabulary mastery, but the results are not satisfactory. They were only able to achieve an average score of 42, far below the minimum criteria of mastery leaning, which is 75. It was because the students are less motivated to master it. Quantitative research with experimental design was carried out to test Kahoot! media, one of the game-based learning methods to improve students’ vocabulary learning outcomes in class X MAN 4 HST. The results showed that students' learning outcomes in the experimental class which used Kahoot! Gamification method is significantly higher than the control class, which used reading aloud and guessing the meaning method. The average learning outcomes in the experimental class were 28,269 points higher than that of the control class. The average value of the control class N-Gain is 25.95, which is categorized as ineffective. While the average N-Gain value of the experimental class is 74.31, categorized as quite effective category. The results indicated that Kahoot! implementation can increase the average score of students in learning mufradat to 85.